Development of Learning Media to Improve Students' Higher Order Thinking Skills in Circular Motion Material - Zulhelmi Zulhelmi; Naila Fauza; Dina Syaflita; Juli Pratiwi; Tommy Tanu Wijaya; Neni Hermita (Postgraduate, University of Mataram, 2023)
The purpose of this research is to develop learning media that can improve students' Higher Order Thinking Skills (HOTS) on the topic